The portrayal of panic-buying and stockpiling in English newspapers during Covid, a mixed-method content analysis - Dayna Brackley; Rebecca Wells (PLoS ONE, 2025)
Panic-buying and stockpiling during Covid disrupted the supply chain, causing food shortages and impacting the vulnerable. The government faced criticism for its lack of food system resilience, poor communications planning, and reliance on retailers. The British media frequently reported on panic-buying during early lockdown stages in 2020 and throughout Covid. The media play an important role in communicating information to the British public during times of crisis and influence public opinion. This mixed-method study examined English media portrayal of panic-buying, analysing text and visual data from six of the highest-circulating newspapers from March to July 2020. It reviewed reporting trends, use of imagery, themes, and prominent stakeholder voices. Content analysis of 209 articles showed that coverage was dominated by popular and left-wing press, with 89% of articles using sensationalised language and 68% coded as negative. In a subset of 125 articles, visual imagery showed empty shelves in 64% of analysed images, reinforcing the impression of food shortages. Supermarkets were the most quoted stakeholders, appearing in 62% of articles. Contradictions included reports of no food shortages alongside images of empty shelves and early newspaper advice encouraging stockpiling. Reporting peaked between March 16–22, 2020. Six key themes were identified: supermarket prominence, food supply/access, food policy, individual behaviour, socio-economic impacts, and panic-buying drivers—all themes had relevance to food system resilience. Future civil unrest linked to food-system challenges, potentially driven by climate change, conflict, or political instability, could see panic-buying play a significant role. Research on media portrayals of panic-buying can help policymakers enhance communication strategies and identify critical issues during crises. The Covid pandemic revealed crucial lessons about the media’s potential role in shaping public behaviour, highlighting the need for stronger government communication and collaboration with both the media and retailers to ensure consistent messaging, particularly to protect vulnerable groups.